Optimization, characterization and biological activity of siderophore produced by marine Streptomyces coelicolor - Benazir Begum Sirajudeen; Jenifer Annis Christy Joseph Sahayaraj; Lok Kirubahar Sankararamalingam; Raja Roobia Rajendran; Murugappan Ramanathan; Padmavathy Sethuramasamy (PLoS ONE, 2026)
Two Streptomyces spp. were isolated from open ocean waters of the Gulf of Mannar. Of the two isolates, one was identified as Streptomyces coelicolor through conventional and molecular approaches, and it was found to produce a siderophore. Characterization revealed the siderophore to be of trihydroxamate type with hexadentate iron-binding capacity. FTIR analysis indicated the presence of aromatic rings with C–O and C = C stretching, while 1 H and 13 C NMR together with mass spectrometry confirmed the hydroxamate nature and identified the siderophore as ferrioxamine. A narrow shift in λ max indicate the photoreactive nature of the siderophore on exposure to sunlight. The cell-free supernatant of S. coelicolor and the purified siderophore dose-dependently inhibited the growth of microbial pathogens. Quorum quenching activity was confirmed using the indicator strain Chromobacterium violaceum . Both the cell-free supernatant and siderophore were found to inhibit biofilm formation and induce reactive oxygen species (ROS) generation in pathogens. The siderophore also suppressed the proliferation of the breast cancer cell line (MCF-7) by disturbing iron homeostasis. Optimization of International Streptomyces Project (ISP2) medium constituents using two-level factorial design and response surface methodology (RSM) enabled cost-effective siderophore production. In addition to iron, the siderophore exhibited binding affinity for other heavy metals including zinc, cobalt, cadmium, lead, and magnesium.